Inhibition of light-induced stomatal opening by allyl isothiocyanate does not require guard cell cytosolic Ca2+ signaling. (27th February 2020) - Ye, Wenxiu; Ando, Eigo; Rhaman, Mohammad Saidur; Tahjib-Ul-Arif, Md; Okuma, Eiji; Nakamura, Yoshimasa; Kinoshita, Toshinori; Murata, Yoshiyuki
Abstract: The glucosinolate–myrosinase system is a well-known defense system that has been shown to induce stomatal closure in Brassicales. Isothiocyanates are highly reactive hydrolysates of glucosinolates, and an isothiocyanate, allyl isothiocyanate (AITC), induces stomatal closure accompanied by elevation of free cytosolic Ca 2+ concentration ([Ca 2+ ]cyt ) in Arabidopsis. It remains unknown whether AITC inhibits light-induced stomatal opening. This study investigated the role of Ca 2+ in AITC-induced stomatal closure and inhibition of light-induced stomatal opening. AITC induced stomatal closure and inhibited light-induced stomatal opening in a dose-dependent manner. A Ca 2+ channel inhibitor, La 3+, a Ca 2+ chelator, EGTA, and an inhibitor of Ca 2+ release from internal stores, nicotinamide, inhibited AITC-induced [Ca 2+ ]cyt elevation and stomatal closure, but did not affect inhibition of light-induced stomatal opening. AITC activated non-selective Ca 2+ -permeable cation channels and inhibited inward-rectifying K + (K + in ) channels in a Ca 2+ -independent manner. AITC also inhibited stomatal opening induced by fusicoccin, a plasma membrane H + -ATPase activator, but had no significant effect on fusicoccin-induced phosphorylation of the penultimate threonine of H + -ATPase. Taken together, these results suggest that AITC induces Ca 2+ influx and Ca 2+ release to elevate [Ca 2+ ]cyt, which is essential for AITC-induced stomatal closure but not for inhibition of K + in channels and light-induced stomatal opening. Abstract : Allyl isothiocyanate (AITC) induces Ca 2+ influx and Ca 2+ release to elevate [Ca 2+ ]cyt, which is essential for AITC-induced stomatal closure but not for inhibition of K + in channels or light-induced stomatal opening.